High Incidence of Epileptiform Potentials During Continuous EEG Monitoring in Critically Ill COVID-19 Patients - Schultz, Barbara; Krauß, Terence; Schmidt, Maren; Schultz, Michael; Schneider, Andrea; Wiesner, Olaf; Schmidt, Julius J.; Stahl, Klaus; David, Sascha; Hoeper, Marius M.; Busch, Markus (Frontiers in Medicine, 2021)
Abstract Objective: To analyse continuous 1- or 2-channel electroencephalograms (EEGs) of mechanically ventilated patients with coronavirus disease 2019 (COVID-19) with regard to occurrence of epileptiform potentials. Design: Single-center retrospective analysis. Setting: Intensive care unit of Hannover Medical School, Hannover, Germany. Patients: Critically ill COVID-19 patients who underwent continuous routine EEG monitoring (EEG monitor: Narcotrend-Compact M) during sedation. Measurements and Main Results: Data from 15 COVID-19 patients (11 men, 4 women; age: 19 to 75 years) were evaluated. Epileptiform potentials occurred in 10 of 15 patients (66.7%). Conclusions: The results of the evaluation regarding the occurrence of epileptiform potentials show that there is an unusually high percentage of cerebral involvement in patients with severe COVID-19. EEG monitoring can be used in COVID-19 patients to detect epileptiform potentials.